An integrative approach to narrative therapy and eye movement desensitization and reprocessing (EMDR) - De Villiers, Elizabeth Fredericka (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEdPsych)--University of Stellenbosch, 2005.